THE STANDARDS FOR ENSURING THE QUALITY OF EDUCATION IN KOSOVO ACCORDING TO EUROPEAN STANDARDS OF THE HIGH EDUCATION - Krasniqi, Sc. Safet (International Journal of Research -GRANTHAALAYAH, 2018)
Ensuring the existing capacities as a basic condition for a quality education, in education is connected in the beginning with a level of consciousness that captures in itself the need of educational planning building. These mechanisms despite that they are legal it has also to do with building up the capacities through twinning projects, funded by EU. The planning process has started by the SWOT program. The analyses showed weak points for ensuring the quality in education and they are separation of responsibilities between institutions. What is indispensable in Kosovo, it is building mechanisms to ensure quality assessment. The methods used in this paper are more research of materials and less comparative as far as the course and previous actions in Kosovo education. It is approved and entered into effect the law for education and capacity enhancement in Kosovo that aims supplying the people of all ages with professional knowledge. During the theses paper we are going to elaborate wider many theoretical and practical issues which deal with intentions, strategies and European standards which coordinate possibilities of accomplishment of objectives and ranking Kosovo education within education of European countries.